ANTESEDEN DARI NIAT PERILAKU PEMBELIAN PRODUK RAMAH LINGKUNGAN - Giri Prahasta; Luki Adiati Pratomo (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2016)
This research aims to examine the effect of consumers attitude toward the protection of the environment,personal norms related to green issues, and consumers willingness to pay for green product attributes on theintention to green purchasing behavior . The data was gathered by using questionnaires and was collectedfrom 153 respondents who had bought organic food in Jakarta. The sampling technique used is purposivesampling. Mutiple Regression is used to analyze the data. The findings showed that those antecedences ofintentions to green purchasing behavior that consists of the consumers attitude toward the protection of theenvironment, personal norms related to green issues, and consumers willingness to pay for green productattributes have positive influence on intention to green purchasing behavior. For future research it issuggested to research other green products in addition to organic food products and add other variables.